2008
DOI: 10.1186/1754-9493-2-24
|View full text |Cite
|
Sign up to set email alerts
|

Standardised proformas improve patient handover: Audit of trauma handover practice

Abstract: This audit highlights the issue of data transfer between shifts. Standardised proformas encourage filling of relevant fields and increases the data transferred between shifts thereby reducing the potential for clinical error cause by shift patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 4 publications
(9 reference statements)
2
57
0
Order By: Relevance
“…Ferran et al studied the use of standardised proformas to improve patient handover, auditing information handover for trauma patients before and after the introduction of a proforma. 11 Standardised proformas led to significantly less information loss, however, some information was still poorly handed over even with the proformas. Grainge et al have shown a standardised weekend handover form can improve documentation, for example of resuscitation decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Ferran et al studied the use of standardised proformas to improve patient handover, auditing information handover for trauma patients before and after the introduction of a proforma. 11 Standardised proformas led to significantly less information loss, however, some information was still poorly handed over even with the proformas. Grainge et al have shown a standardised weekend handover form can improve documentation, for example of resuscitation decisions.…”
Section: Discussionmentioning
confidence: 99%
“…The topics covered on our checklist include those used in previously developed checklists, including diagnosis, comorbidities, history, mechanism of injury and outstanding injuries. 5,[7][8][9]12 It is important to remember that our checklist is not exclusive; it contains a column for "other pertinent information" to address the variability among patients who present with traumatic injuries. The checklist provides a starting point for information that should not be missed, but as seen in Table 2, most of the information has been deemed important by a panel of orthopedic surgeons and trainees across the country and any can be added at the discretion of the admitting physician.…”
Section: Discussionmentioning
confidence: 99%
“…5,9 The British Medical Association (BMA) has advocated that every hospital should have their own handover policy and specify who should be involved, when handover should take place, where it should occur and what needs to be handed over. 1 Therefore, the purpose of the present study was to identify and survey Canadian Orthopaedic Association (COA) members about the vital clinical information needed for the development of a standardized, preoperative handover checklist for use with trauma patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on what information needed to be transmitted communication should be either verbal [51] or in writing [34] as free text or structured forms [41]. Four of the structured forms described in detail were derived from the SBAR method or modified it [45,55,56,58], but also other generic mnemonics [42,47,54], specific checklists [48,57] or minimum data sets [49,52] were used.…”
Section: Mode and Structure Of Communicationmentioning
confidence: 99%